Assessment of reflective insulation systems in wall application in hot-arid climates. (January 2020) - Pourghorban, Arash; Kari, Behrouz Mohammad; Solgi, Ebrahim
Highlights: Assessment of reflective systems in steady-state and climatic conditions. Calculated R-values by ISO 15099 are in good agreement with ASHRAE. Systems with airspace thickness of 20 mm are the optimized configurations. The R-value increases on the coldest day. South facing systems thermally perform the best on the hottest day. Abstract: Reflective insulation systems are among the most effective energy efficient products for application in arid climates. Previous studies focused on reflective air spaces (rather than reflective insulation systems) in laboratory steady-state conditions, and different defects and limitations in those investigations have made it necessary to probe for patterns to address the research key questions and generalization of the results. Thus, in this study a numerical simulation approach using ISO 15099 is utilized for performing calculations in enclosed reflective air spaces. Additionally, application of ISO 15099 is compared with ASHRAE experimental data, and related differences and limitations are demonstrated. The optimized configurations of the reflective insulation systems in wall application are explored, and an unprecedented extensive climatic evaluation is conducted. Moreover, the influences of extreme climatic conditions and orientation factor on thermal performance of various reflective configurations are assessed. It is found that systems with a 20 mm air gap adjacent to reflective surfaces are the most appropriate systems in the wall application. In addition, thermal performance of these systems is highly affected by environmental conditions. Finally, the optimized orientations in each configuration are presented.